Effectiveness of highly active antiretroviral therapy (HAART) used concomitantly with rifampicin in patients with tuberculosis and AIDS - Sant'Anna,Flávia Marinho (2009)
This study evaluated the effectiveness of two HAART regimens concomitant to rifampicin based tuberculosis (TB) treatment. Patients with TB/HIV diagnosis followed at the TB program between June 2000 and March 2005 were prospectively evaluated. The different HAART regimens in antiretrovirals (ARV) treatment naïve and ARV experienced patients were compared. The effectiveness of HAART was defined as a VL <80 copies/mL from month 4 to month 10 after TB treatment. One hundred and forty-two patients were included. Among these, 68 (47%) were treatment naïve and 76 (53%) previously exposed. Odds ratio (OR) in naïve patients treated with efavirenz (EFV) based regimen (n=42) compared to ritonavir/saquinavir (RTV/SQV) based regimen (n=26) was 8.0 (CI=1.67-38.35, p=0.008). OR from ARV experienced patients treated with RTV/SQV based regimen compared to EFV was 3.08 (CI=0.65-14.6, p=0.15), although with no statistical significance. Better effectiveness and tolerability were observed in antiretrovirals treatment naïve patients using EFV based regimens. Although not statistically significant, a favorable virologic response and a better tolerability were observed in the ARV experienced patients group who received a RTV/SQV based regimen.